2021
DOI: 10.3390/s21248286
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Gait Analysis Pipeline for Wearable Sensors: A Pilot Study in Parkinson’s Disease

Abstract: The use of wearable sensors allows continuous recordings of physical activity from participants in free-living or at-home clinical studies. The large amount of data collected demands automatic analysis pipelines to extract gait parameters that can be used as clinical endpoints. We introduce a deep learning-based automatic pipeline for wearables that processes tri-axial accelerometry data and extracts gait events—bout segmentation, initial contact (IC), and final contact (FC)—from a single sensor located at eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…A possible explanation for these results is the signal noise caused by the integration procedure applied as part of the inverted pendulum gait model used for obtaining these parameters from acceleration time series [ 43 ]. Analysis of gait data with neural networks may lead to more promising results [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for these results is the signal noise caused by the integration procedure applied as part of the inverted pendulum gait model used for obtaining these parameters from acceleration time series [ 43 ]. Analysis of gait data with neural networks may lead to more promising results [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agreement of the OneStep app with different reference standards (APDM Mobility Lab, Zeno walkway) was higher for gait speed (ICC = 0.94, Pearson correlation coefficient [ r ] = 0.89–0.91) and step length (ICC = 0.80, r = 0.65–0.84) than for double limb support (ICC = 0.52, r = 0.61– 0 .62). The lower validity for measuring double support time has also been reported for stand-alone IMUs in normal 68 and pathological gait 69 , 70 . As previously discussed, the difficulty of accurately detecting both heel strike and toe-off for estimating this gait parameter has often been mentioned in this context as a potential reason for greater measurement errors with this gait parameter 65 67 , which may also be the case for the Health app.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies also suggested that the waist and upper limbs were the optimal locations for collecting kinematic parameters in patients with PD ( 41 , 52 54 ). Peraza et al ( 55 ) proposed an automatic gait analysis process based on DL algorithms, with data sourced from triaxial accelerometers placed on the lower limbs, trunk (waist), and upper limbs. The results showed that data from single triaxial accelerometers on the lower limbs and trunk (waist) performed better than those from the upper limbs in assessing gait in patients with PD and healthy elderly people ( 55 ).…”
Section: Discussionmentioning
confidence: 99%